Genital Human Papillomavirus Infection in Women Who Have Sex with Women - Marrazzo, Jeanne M.; Koutsky, Laura A.; Stine, Kathleen L.; Kuypers, Jane M.; Grubert, Thomas A.; Galloway, Denise A.; Kiviat, Nancy B.; Handsfield, H. Hunter (The Journal of infectious diseases, 1998)
Genital infection with human papillomavirus (HPV), as determined by polymerase chain reaction detection of HPV DNA and prevalence of HPV-6 and -16 serum antibodies, was investigated in 149 women who were sexually active with women. By use of HPV L1 consensus primers and hybridization to types 6/11, 16, 18, 31/33/35/39, and 45 and a generic probe, HPV DNA was detected in 30% of subjects; of these, 20% had type 31/33/35/39, 18% had type 16, and 2% had type 6/11. Of 21 subjects reporting no prior sex with men, HPV DNA was detected in 19% and squamous intraepithelial lesions in 14%. By capture ELISA with HPV-6 and -16 L1 capsids, 47% of subjects were seropositive for HPV-16 and 62% for HPV-6. Current smoking was associated with detectable HPV DNA. Genital HPV infection and squamous intraepithelial lesions are common among women who are sexually active with women and occur among those who have not had sex with men.